A Mixed-Binary Linear Model for Fleet Routing and Multiple Product-Types Distribution - Tapia, Cesar G. (Philippine Management Review; Vol 6 (1995), 2016)
This paper presents a mathematical programming approach to solving the problem of routing a fleet of vehicles for the distribution of a number of product-types in a network where each node represents a client with specific demands.  The proposed mathematical model utilizes binary and real valued decision variables and linear formulations of the objective function and the constraints.